The Importance of Ethics in Communication Toward Children: An Islamic Overview - Dewi Suriyani Djamdjuri; Fadia Holisah (Al-Aulad: Journal of Islamic Primary Education, 2021)
The concept of communication is not only related to the problem of how to speak effectively but also the ethics of speaking. Since entering the reform era, the Indonesian people have been in an atmosphere of euphoria, free to talk about anything, to anyone, in any way. Al-Qur'an mentions communication as one of human nature, hence, it is importance to understand how important to communicate in good manner, especially toward children, as we know that children learn a lot from what they see, hear and imitate. To find out how humans should communicate, Qur'an provides keywords related to this. The researchers conducted literature review from some related research articles discussing the importance of this issue. The commandment stated in Quran and hadith are indication of the obligation for Muslims to apply the nature of honesty and correct speech in which it is known as qaulansadidan. A person's success is not determined by intelligence only but also emotion. To accomplish, communication ethics are really important to be sophisticated toward children. Educate the children with good daily communication ethics affects their life and facilitate them to achieve genuine success.